PERTUMBUHAN BIBIT KAYU PUTIH (Melaleuca cajuputi) PADA BERBAGAI KOMBINASI KOMPOS SERESAH DAUN KIARA PAYUNG (Filicium sp) DAN PUPUK KANDANG SEBAGAI MEDIA SAPIH - Nur Kholifah Rahmawati; Emmy Winarni; Damaris Payung (Jurnal Sylva Scienteae, 2020)
This research aims to know the percentage of life on each treatment and to analyze the growth response of kayu putih (Melaleuca cajuputi) to the Various combination of Filicium sp. leaf litter compost and manure as seedling media. This research was held at Shadehouse Faculty of Forestry University of Lambung Mangkurat Banjarbaru, for 3 months. The data was analyzed using Completely Randomized  Design (CRD) with 4 treatments and 10 replications, so it gained 40 experiment units. The treatments were A =Top soil 100% as control, B = Top Soil + Filicium Leaf Litter Compost.  C =  Top Soil + Filicium Leaf Litter Compost + Cow Manure. D = Top Soil + Filicium Leaf Litter Compost + Goat Manure. The results showed that living percentage was 100%  for each treatment. The ANOVA shows there was non significant differences for all treatments and all growth parameters (increase in height and trunk diameter). Combination of seedlings media Top Soil + Filicium Leaf Litter Compost + Goat Manure (D) showed the best growth to all parameters (increase in height 17.6 cm and trunk diameter 1.03 mm). Goat manure in the media composition is able to increase the seedlings growth. Keywords: Growth; Kayu Putih; Filicium Litter Compost